Reading Learning Management in Meeting Parental Expectations in Early Childhood Education - Anna Pebriani; Waska Warta (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to analyze the management of reading instruction in early childhood education to fulfil parental expectations for children’s reading competence. The research employed a qualitative approach with a multisite case study design conducted at TK Negeri Tambora 01 and PAUD Pelita Hati in Jakarta. Data were collected through in-depth interviews, observations, and document analysis involving school principals, teachers, and parents. Data analysis was carried out using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that reading learning management is implemented through four main stages: planning, organizing, actuating, and controlling. In the planning stage, learning activities are designed based on children’s developmental needs while considering parental expectations. In the organizing stage, coordination among teachers and collaboration with parents support the learning process. In the implementation stage, reading learning is conducted through play-based, interactive, and technology-supported activities that enhance children’s engagement. In the controlling stage, evaluation is carried out through observation and parental feedback, followed by continuous improvement through follow-up activities. The study concludes that effective reading learning management requires a balanced approach that integrates developmentally appropriate practices with parental expectations. Parental involvement plays a significant role in supporting children’s literacy development, but it must be managed carefully to avoid excessive pressure. This study contributes to understanding how learning management can be adapted to foster meaningful and sustainable early literacy development in early childhood education.